Telaah Hermeneutika Kritis terhadap Femisida dalam Perspektif Al-Qur'an serta Relevansinya terhadapa Pendidikan Agama Islam - abror, indal; Al-Faiz Muhammad Rabbany Tarman; Tri Wulandari (UIN Sunan Kalijaga Yogyakarta, 2024)
Gender injustice that seems to be legitimized by normative texts is seriously challenged by problems of interpretation. This research is a library research and qualitative. The author focuses on Femicide in the Perspective of the Qur'an: A Critical Hermeneutic Analysis and its Relevance to Islamic Religious Education. Femicide is a criminal act of sadistic murder based on hatred of women committed by men. In the Qur'anic perspective, it is substantially described in four verses, namely QS. al-An'am 6: 137, QS. At-Takwir 81: 8, QS. An-Nahl 16: 59 and QS. This is a historical fact as documented in several Prophetic traditions. Femicide behavior in pre-Islamic times should be reinterpreted according to the times. The word can be understood to mean sadistic behavior such as being mutilated, abused, burned, crushed, and so on. Femicide is relevant to discuss because PAI plays an important role in shaping human values and attitudes. PAI has the potential to be an effective tool in instilling aspects of humanity, justice, and respect for human rights, including women's rights.